A fuzzy approach to option pricing in a Levy process setting - Nowak, Piotr; Romaniuk, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
In this paper the problem of European option valuation in a Levy process setting is analysed. In our model the underlying asset follows a geometric Levy process. The jump part of the log-price process, which is a linear combination of Poisson processes, describes upward and downward jumps in price. The proposed pricing method is based on stochastic analysis and the theory of fuzzy sets.
Keywords: option pricing; Levy processes; minimal entropy martingale measure; fuzzy sets; Monte Carlo simulation